Effect of steroid hormones on the innate immune response induced by Staphylococcus aureus in the goat mammary gland. (12th March 2017) - Kuwahara, K; Yoshimura, Y; Isobe, N
Contents: The objective of this study was to compare the dynamics of innate immune components after intramammary infusion of Staphylococcus aureus (SA) under conditions of high oestrogen and high progesterone in goats. In one group ("E‐group"), controlled internal drug release (CIDR) devices were inserted intravaginally from days −11 to −4. Prostaglandin F2α was administered immediately after removal of the CIDR device at day −3, and then oestradiol benzoate (E) was injected intramuscularly once a day from days −2 to 3. Heat‐inactivated SA was then administered via intramammary infusion to the left udder at day 0, whilst only saline was infused to the right udder as a control. In a second group ("P‐group"), CIDR devices were inserted intravaginally from days −3 to 7 and SA was infused at day 0 in the same way as in the E‐group. The milk yield and the concentration of innate immune components (somatic cell count (SCC), lactoferrin (LF), S100A7 and goat ß‐defensin 1 (GBD‐1)) in the milk were measured. Milk yield decreased drastically in both SA and control udders in the E‐group, whereas the P‐group exhibited increased milk yield in both SA and control udders. SCC increased after SA infusion in both E‐ and P‐groups, although it was higher in the E‐group than in the P‐group. There was no significant change in LF concentration in the E‐group, but a decrease was observed in the P‐group. Concentrations of S100A and GBD‐1 were significantly increased after SA infusion in the E‐group but not in the P‐group. These results suggest that E enhances the innate immune response induced by SA in the goat mammary gland. This effect may be due to the reduction in milk yield and upregulation of innate immune components.